Roles of Administrators in Early Childhood Centers Towards Early Childhood's Holistic Development Based on 3D Knowledge Foundation for Early Childhood Development - Surinchompoo, Dr.Chatwilai (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2023)
Roles of the administrators in early childhood schools in holistic childhood development based on 3D foundational knowledge for early childhood development are guidelines for academic administration in the present where the situations in this world change rapidly. Educational institution administrators and all those involved with early childhood education should have knowledge and understanding and support for all parties so that the schools can work efficiently. These are consisted of vision and mission plans to develop the quality of early childhood education for the development of early childhood in terms of organizing learning experiences and parenting consistent the promotion of 21st century skills. These skills include learning and innovation skill, life and occupational skill, and information technology skill integrated holistically on 3D foundational knowledge which is consisted of 3 parts: 1) self-development (SELF), 2) development of brain skills or EF (Executive Function), and 3) the development in all 4 areas. Consequently, the roles and duties of administrators are such important burden in organizing effective early childhood education. The administrators should realize the changes, develop oneself to be an excellent leader and modernize the organization, develop the team to be learning people, and be “actual administrators” in educational institutions as the leaders in applying various guidelines to develop the quality of education and lead the government's educational policy into practice in order to develop educational institutions, teachers, personnel, and children with quality. The management guidelines for early childhood educational institutions according to the concept of holistic development based on 3D foundational knowledge for early childhood development to manage educational institutions consisted of following principles: 1) Administering educational institutions according to the guidelines for self-development (SELF) is management based on an understanding of teachers' behavior, feelings, connections, and beliefs in their performance where educational institution administrators are the ones who help, support, develop, and are academic leaders for teachers with identity; 2) Administering educational institutions according to the guidelines for developing brain skill or EF (Executive Function), which is management based on guidelines for managing thoughts and emotions, feelings, behavior, and providing opportunities based on the development of teachers' true potential and abilities with an understanding of self-development (SELF). Administrators are the ones who help, support, and develop teachers according to the elements of EF (Executive Functions) in 9 aspects to become teachers' working skill. In this case, the administrators can encourage and develop teachers to be successful in their work, able to solve their problems, and can adapt for living in working society happily. It can also help teachers survive difficult situations and be able to set their goal and plan to achieve that goal by creating the environment and opportunities to learn about their own performance, deal with emotions, and contemplation, and can manage themselves in many ways which uses management principles of 9 skills of EF; and 3) administrating the educational institution according to the development guidelines in all 4 aspects which is the management aiming to develop teachers to have potential consistent with the development of all 4 areas according to teachers' potential. According to the results of management in 1 and 2 as mentioned above, it will be possible to make aspect 3 of the personnel management in educational institutions of administrators achieve effective results. The teachers' performance is aligned with the goals of holistic child development based on 3D knowledge foundation for early childhood development.